Transition metal modification and carbon vacancy promoted Cr2CO2 (MXenes): a new opportunity for a highly active catalyst for the hydrogen evolution reaction. Issue 42 (17th October 2018) - Cheng, Yu-Wen; Dai, Jian-Hong; Zhang, Yu-Min; Song, Yan
Abstract : Transition metal (TM) modification and carbon vacancy engineering promoted the hydrogen evolution reaction (HER) catalytic activity of Cr2 CO2 . Abstract : Electrocatalysis has the potential to become a more sustainable approach to generate hydrogen as a clean energy carrier. Developing alternatives to precious metals (Pt, Pd and Ir) for hydrogen production from water splitting is central to the area of renewable energy. Two-dimensional metal carbide and nitride (MXenes) materials have shown characteristics of promising catalysts for the hydrogen evolution reaction (HER). Herein, we performed density functional calculations to predict the stability and electrocatalytic performance of 2D Cr2 CO2 with transition metal modification and carbon vacancy engineering. Our results indicated that pure Cr2 C and Cr2 CO2 MXenes are conductive, which was favorable to the charge transfer during the HER. The Cr2 C MXenes tend to be fully terminated by O* under standard conditions [pH = 0, p (H2 ) = 1 bar, and U = 0 V vs. standard conditions]. The modification by transition metals could tune the Gibbs free energy of reaction for the adsorption of atomic hydrogen (Δ G H* ) on Cr2 CO2 to close to 0 eV (ideal value) at suitable TM coverage. Charge transfer analysis suggested that surface O atoms gain more electrons by the transition metal doping, and therefore weaken the bonding interaction with H atoms to compare with that of pure Cr2 CO2 . The HER performance of Cr2 CO2 can also be improved via carbon vacancy engineering. These results indicated that transition metal surface modification and carbon vacancy engineering are effective ways for achieving promising HER electrocatalysts for water splitting.